The Küme Mongen and the Reign of God - Del Villar, M. Soledad (Lumen et Vita, 2018)
This paper attempts to offer a theological reflection that compares two concepts from two different religious traditions that deal with a similar concern: guiding humanity and the cosmos to flourishing and abundant life. On the one hand, I will consider the Küme Mongenthat comes from the Mapuche people of Chile and Argentina. On the other hand, I will consider the concept of the reign of God, so central to the Gospels and re-articulated frequently in Christology, specifically, Latin-American liberation theology. First, I will explain the context from which Küme Mongenemerges and give an account of the central ideas of this concept. Second, I will give an account of the treatment of the reign of God in J.A. Pagola and J. Sobrino’s Christology. Finally, I will explore the possible connections between the Mapuche vision of fruitful life and the Kingdom of God, opening possible paths for mutual learning and understanding between the Mapuche and the Christian religious traditions.